2001
DOI: 10.1364/ol.26.000325
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrary-lattice photonic crystals created by multiphoton microfabrication

Abstract: We used voxels of an intensely modified refractive index generated by multiphoton absorption at the focus of femtosecond laser pulses in Ge-doped silica as photonic atoms to build photonic lattices. The voxels were spatially organized in the same way as atoms arrayed in actual crystals, and a Bragg-like diffraction from the photonic atoms was evidenced by a photonic bandgap (PBG) effect. Postfabrication annealing was found to be essential for reducing random scattering and therefore enhancing PBG. This techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(82 citation statements)
references
References 17 publications
1
79
0
1
Order By: Relevance
“…Type I modification has been used to achieve waveguides and couplers, 1), 3) whereas type III-fs void like defects have been exploited for data storage and photonic crystals. 4), 5) The intermediate type II-fs regime has received little attention until now but indeed seems to have intriguing properties. Type II-fs structures were first observed in Ge-doped silica where they show an anisotropic light scattering that is dependent on the plane of polarization of the light.…”
Section: Introductionmentioning
confidence: 99%
“…Type I modification has been used to achieve waveguides and couplers, 1), 3) whereas type III-fs void like defects have been exploited for data storage and photonic crystals. 4), 5) The intermediate type II-fs regime has received little attention until now but indeed seems to have intriguing properties. Type II-fs structures were first observed in Ge-doped silica where they show an anisotropic light scattering that is dependent on the plane of polarization of the light.…”
Section: Introductionmentioning
confidence: 99%
“…So far, pressures in excess of 0.1 TPa have been obtained using a diamond anvil in stationary conditions, while transient pressures behind shock waves generated by chemical or nuclear explosions or generated using powerful lasers up to 50 TPa have been reported [1,2]. Here we present experimental evidence that one can create TPa pressures, many times the strength of any material, using low energy pulses from a conventional tabletop laser.Recent studies have demonstrated [3][4][5][6][7][8] that sub-ps laser pulses tightly focused inside transparent dielectrics (glasses, crystals, and polymers) can produce detectable sub-micrometer-sized structural modifications, including voids. This requires intensities in excess of 10 14 W=cm 2 which results in a highly nonlinear light-matter interaction with most dielectrics being ionized early in the laser pulse.…”
mentioning
confidence: 99%
“…Recent studies have demonstrated [3][4][5][6][7][8] that sub-ps laser pulses tightly focused inside transparent dielectrics (glasses, crystals, and polymers) can produce detectable sub-micrometer-sized structural modifications, including voids. This requires intensities in excess of 10 14 W=cm 2 which results in a highly nonlinear light-matter interaction with most dielectrics being ionized early in the laser pulse.…”
mentioning
confidence: 99%
“…A review that outlines the fundamental principles of [LIPS] relevant to sample surface studies is given by Vadillo et al [63]. This review discusses the experimental parameters governing its spatial resolution and presents the applications concerning surface examination.…”
Section: Review Of Some Literatures On Laser Radiation Interaction Wimentioning
confidence: 99%